The Effect of Quality of Service, Facility and Location on Registration Decision at SMK Telkom 2 Medan - Muhammad Taufik Lesmana; Asrizal Efendy Nasution (AIBPM Publisher, 2019)
This study aims to determine the effect of service quality, facility and location on decision to register at SMK Telkom 2 Medan. The results of this study indicate that there is a significant effect on the quality of service on decision to register because the value of tcount > ttable of 3.310 > 1.9913 and the significance value of 0.001 < 0.05 is in the area of rejection H0 and Ha received, the facility shows there is a significant influence on decision to register because it has a value of tcount > ttable of 2.967 > 1.9913 and its significance value 0.004 < 0.05 is in the area of rejection H0 and Ha accepted, the location shows there is a significant influence on decision to register because it has a value of tcount > ttable of 3.173 > 1.9913 and the significance value 0.002 > 0.05 are in the area of rejection of H0 and Ha are accepted. Based on the results of simultaneous testing it can be seen that the calculated Fcount > F table is 24.667 > 2.72 and the significance value is 0.000 > 0.05, it can be concluded that the variable quality of service (X1), facility (X2), and location (X3) have a significant effect simultaneously on the register decision variable (Y).